Stakeholder‐driven principles for advancing equity through shared measurement. (22nd July 2022) - Hilliard‐Boone, Tandrea; Firminger, Kirsten; Dutta, Tania; Cowans, Tamika; DePatie, Holly; Maurer, Maureen; Schultz, Ellen; Castro‐Reyes, Paige; Richmond, Al; Muhammad, Michael; Pathak‐Sen, Ela; Powell, Wizdom
Abstract: Objective: To advance equity by developing stakeholder‐driven principles of shared measurement, which is using a common set of measurable goals that reflect shared priorities across communities and systems, such as health care, public health, and human and social services. Data Sources: From October 2019 to July 2021, we collected primary data from leaders in cross‐systems alignment, measurement, and community engagement—including community members and community‐based organization leaders—across the United States. Study Design: In partnership with equity and community engagement experts, we conducted a mixed‐methods study that included multiple formative research activities and culminated in a six‐week, stakeholder‐engaged modified‐Delphi process. Data Collection: Formative data collection occurred through an environmental scan, interviews, focus groups, and an online survey. Principles were developed using a virtual modified Delphi with iterative rapid‐analysis. Feedback on the final principles was collected through virtual focus groups, an online feedback form, and during virtual presentations. Principal Findings: We developed a set of five guiding principles. Measurement that aligns systems with communities toward equitable outcomes: (1) Requires upfront investment in communities; (2) Is co‐created by communities; (3) Creates accountability to communities for addressing root causes of inequities and repairing harm; (4) Focuses on a holistic and comprehensive view of communities that highlights assets and historical context; and (5) Reflects long‐term efforts to build trust. Using an equity‐focused process resulted in principles with broad applicability. Conclusions: Leaders across systems and communities can use these shared measurement principles to reimagine and transform how systems create equitable health by centering the needs and priorities of the communities they serve, particularly communities that historically have been harmed the most by inequities. Intentionally centering equity across all project activities was essential to producing principles that could guide others in advancing equity.